Evaluasi Efektivitas Penggunaan Metode Cooperative Learning dalam Pembelajaran IPA di Sekolah - Handayani, Rina; Pertiwi (Papanda Publisher, 2022)
This study aims to evaluate the effectiveness of Cooperative Learning method implementation in teaching Natural Sciences (IPA) at Buntu II Elementary School. The research method used is a quantitative approach with a quasi-experimental design, involving fourth-grade students with a total of 60 students as research subjects. Data were collected through pretest and posttest to measure students' understanding before and after the learning intervention, as well as through observations to record student participation and interactions during the learning process. The results show that the understanding of IPA concepts among students who received instruction using Cooperative Learning method is significantly better than students who received conventional instruction. The learning process with Cooperative Learning method also resulted in higher levels of participation and more positive social interactions among students. However, several challenges such as different social skills among students, effective classroom management, and adaptation to diverse learning styles need to be addressed. Recommendations are made to continue and expand the use of Cooperative Learning method in teaching IPA at elementary schools, with measures such as providing training for teachers in effective classroom management and supporting collaboration among students. This research is expected to contribute positively to the development of inclusive and student-centered teaching methods, as well as to improve the quality of education at Buntu II Elementary School and possibly at other schools as well.